2012
DOI: 10.1001/archpediatrics.2011.574
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Prelingually Deafened Adolescents

Abstract: Objectives:To determine the efficacy of cochlear implantation (CI) in prelingually deafened adolescent children and to evaluate predictive variables for successful outcomes.Design: Retrospective medical record review.Participants: Children aged 10 to 17 years with prelingual hearing loss (mean length of deafness, 11.5 years) who received a unilateral CI (mean age at CI, 12.9 years).Intervention: Unilateral CI. Main Outcome Measures: Standard speech perception testing (Consonant-Nucleus-Consonant [CNC]monosylla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 27 publications
(30 reference statements)
3
27
1
Order By: Relevance
“…The fact that the change 3 years postoperatively once again attained statistical significance, even though the observed score remained the same with an even smaller sample size, is presumably due to the higher estimation of the mean, as predicted by the multilevel model. The mean word recognition scores of 44.1% (range 0-88%) and mean sentence recognition scores of 42.4% (range 0-100%) at the 1-year postoperative measurement are comparable to those found in other studies, although it is unclear for some of these studies whether the reported scores were obtained with CI only or in the best-aided condition [Caposecco et al, 2012;Klop et al, 2007;Santarelli et al, 2008;van Dijkhuizen et al, 2011;Yang et al, 2011;Zeitler et al, 2012]. Consistently with the literature, we found extremely large differences between individual word and sentence recognition scores (Fig.…”
Section: Study Objective 1: Changes In Auditory Performancesupporting
confidence: 75%
See 3 more Smart Citations
“…The fact that the change 3 years postoperatively once again attained statistical significance, even though the observed score remained the same with an even smaller sample size, is presumably due to the higher estimation of the mean, as predicted by the multilevel model. The mean word recognition scores of 44.1% (range 0-88%) and mean sentence recognition scores of 42.4% (range 0-100%) at the 1-year postoperative measurement are comparable to those found in other studies, although it is unclear for some of these studies whether the reported scores were obtained with CI only or in the best-aided condition [Caposecco et al, 2012;Klop et al, 2007;Santarelli et al, 2008;van Dijkhuizen et al, 2011;Yang et al, 2011;Zeitler et al, 2012]. Consistently with the literature, we found extremely large differences between individual word and sentence recognition scores (Fig.…”
Section: Study Objective 1: Changes In Auditory Performancesupporting
confidence: 75%
“…Study samples are often small, and a wide range of patient factors are considered that are not uniformly defined across studies. Although not conclusive over all studies, significant relations have been found between CI outcome and a patient's own speech intelligibility [van Dijkhuizen et al, 2016], communication mode [Caposecco et al, 2012;Rousset et al, 2016;Yang et al, 2011;Zeitler et al, 2012], and preoperative speech-understanding scores [Caposecco et al, 2012;Kraaijenga et al, 2016;Rousset et al, 2016;van der Marel et al, 2015;Yang et al, 2011]. At the same time, duration of deafness [Caposecco et al, 2012;Kraaijenga et al, 2016;van der Marel et al, 2015;van Dijkhuizen et al, 2016;Yang et al, 2011] and etiology [Kraaijenga et al, 2016;Zeitler et al, 2012] do not seem to be related to CI outcomes in this patient group.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Similarly, in a review by Zeitler et al of 67 patients with prelingual deafness, post-operative cochlear implant performance was retrospectively studied [18]. The mean age at cochlear implantation was 12.9 years with an associated mean duration of deafness of 11.5 years, representing 61% of patients with "Although studies have revealed no age of implantation-dependent difference in electrically evoked compound action potential of the auditory nerve and brainstem following cochlear implantation … differences have been reported in higher order function along the auditory pathway.…”
Section: Editorialmentioning
confidence: 99%